La impronta de la experiencia migratoria sobre la reinserción sociolaboral post-retorno - Ruiz Núñez, Alfonso (El Colegio de México, 2025)
This paper aims to analyze how the migratory experience affects the labor trajectories of the Spaniards after they return during the pandemic. The article analyzes how experience in different destination cities has different consequences on the development of their labor trajectories, especially on the reinsertion into the labor market of the country of origin. A qualitative longitudinal methodology was used based on a biographical approach, from which 21 subjects with migratory experience were interviewed in Mexico City or London, and at two different observation moments, subjects who experienced a return migration between both observation moments. It was found that, indeed, the migratory experience accumulated in different migratory destination has implications on the socio-labor reintegration experienced after returning to Spain.